Correlational Study of Teacher’s Online Enactment and Students Learning Satisfaction - Hussain, Shafqat; Chang, Ali Gohar; Siyal, Ayaz Latif (Journal of Development and Social Sciences, 2024)
The educational landscape of world is in a crisis situation due to COVID-19 and educational institutions are struggling to adept with the help of technology mediated tools to resume the academic activities. However, at this initial phase of crisis situation, decisions are made, steps and actions have been taken. However, required attention and focus has not been paid while decision and acceptance of online, internet based technologies are made the part of education system. Especially, in Pakistani context where there is digital divide and lack for digital literacy. This quantitative study has been conducted in a private higher secondary school of Sindh, Pakistan. The purpose of study is to include the voice of an important stakeholder i.e. Learner, in the application process of online teaching courses. The study is correlational in its nature and would help us to understand the correlation of Teachers online enactment and Students learning satisfaction. The results of study proved that there is strong correlation between these two variables. This suggests that quality of teachers in terms of online teaching skills along with many other factors such as fairness, assessment methods, positive attitude, subject knowledge and assignment allocation are significant for the satisfaction of students learning needs.